Combined surgical and endovascular treatment of congenital bilateral femoral arteriovenous fistulas in a child: a case report - Xia, Jiejun; Zhang, Liqi; Chen, Kunshan; Wen, Zhe; Huang, Jianzhong; Li, Haibo (Frontiers in Pediatrics, 2025)
BackgroundCongenital arteriovenous fistulas (AVFs) are rare, particularly those involving the bilateral femoral arteriovenous system in an infant. This case report details the successful management of this condition using a combined therapeutic approach.Case presentationWe report the case of a 6-month-old boy who presented with a congenital bilateral femoral arteriovenous fistula, which led to symptoms of fatigue, shortness of breath, and recurrent pneumonia. The patient was successfully treated with a combined therapeutic approach of surgical ligation on the left side and endovascular coil embolization on the right. At the 10-year follow-up, the patient's clinical and echocardiographic status remained normal. The imaging surveillance protocol included regular duplex ultrasound examinations, which confirmed sustained occlusion of both fistulas with no residual dilated veins in the right thigh. The patient remains asymptomatic with no evidence of recurrence.ConclusionThis case highlights the importance of a tailored, combined-modality approach for complex congenital AVFs, especially when the fistulas on each side possess different anatomical characteristics. The specific morphology of the fistula is a critical determinant in choosing the optimal treatment strategy to ensure complete closure and prevent long-term complications such as high-output cardiac failure. This approach serves as a valuable clinical reference for the management of similar complex vascular anomalies in the pediatric population.